Статистичне моделювання факторів формування якості зайнятості в Україні - Корепанов, Олексій Сергійович; Лазебник, Юлія Олександрівна; Момотюк, Людмила Євгеніївна; Парфенцева, Неля Олексіївна; Чала, Тетяна Георгіївна; Корепанов, Георгій Сергійович; Черненко, Дарина Ігорівна; Korepanov, Oleksiy; Lazebnyk, Iuliia; Momotiuk, Liudmyla; Parfentseva, Nelya; Chala, Tеtyana; et al. (Харків : Харківський національний економічний університет ім. С. Кузнеця, 2022)
У статті основна увага приділена розробленню методологічних засад статистичного моделювання факторів формування якості зайнятості. Обґрунтовано необхідність розроблення нової стратегії у формуванні якості зайнятості для забезпечення ефективного соціально-економічно го розвитку України. Визначено необхідні для цього кроки й управлінські рішення. Окреслено проблеми оцінювання якості зайнятості в Україні, основним етапом якого є моделювання факторів формування якості зайнятості з використанням сучасних статистичних методів. З метою визначення узагальнених факторів формування якості зайнятості побудовано модель головних компонент, яка дозволила трансформувати 18-вимірний ознаковий простір у п’ятивимірний простір узагальнених факторів, які пояснюють 87,6% варіації обраних ознак, що свідчить про високий рівень факторизації. Виділено та ранжовано за ступенем значущості п’ять основних факторів: рівень інформатизації суспільства (внесок – 41,7%), умови праці та навколишнє середовище (26,3%), неформальна зайнятість (8,2%), виробничий травматизм зі смертельними наслідками (6,3%) та рівень зайнятості (5,1%). Розрахунки проведені з використанням прикладного пакета «Statistica», зокрема модуля «Factor analysis». Використання розробленої моделі дає можливість запобігти суб’єктивізму при визначенні основних факторів формування якості зайнятості. Проведене дослідження дозволило обґрунтувати теоретико-методологічні засади статистичного моделювання факторів формування якості зайнятості на основі методу головних компонент. Виділені фактори можуть бути прийняті за основу при формуванні ключових напрямків удосконалення сфери зайнятості в Україні.

In the article, the main attention is paid to the development of methodological principles of statistical modeling of factors for the formation of employment quality. The necessity of developing a new strategy in the formation of employment quality to ensure effective socioeconomic development of Ukraine is substantiated. The necessary steps and management decisions are determined. The problems of assessing the quality of employment in Ukraine are outlined, the main stage of which is the modeling of factors for the formation of employment quality using modern statistical methods. In order to define the generalized factors of employment quality formation, a model of the main components is constructed, allowing to transform the 18-dimensional sign space into a five-dimensional space of generalized factors that explain 87.6% of the variation in the selected features, which indicates a high level of factorization. Five main factors are identified and ranked according to the degree of importance: the level of informatization of society (contribution – 41.7%), working conditions and the environment (26.3%), informal employment (8.2%), industrial injuries with fatal consequences (6.3%), and the employment rate (5.1%). The computations were carried out using the application package «Statistica», in particular the module «Factor analysis». The use of the developed model makes it possible to prevent subjectivism in determining the main factors in the formation of employment quality. The conducted study provided to substantiate the theoretical-methodological principles of statistical modeling of factors for the formation of employment quality on the basis of the method of the main components. The identified factors can be taken as a basis for the formation of key directions of improvement of the employment sphere in Ukraine.
Statistical Modeling of the Factors of Formation of the Quality of Employment in Ukraine
Keywords: SOCIAL SCIENCES::Business and economics; SOCIAL SCIENCES::Statistics, computer and systems science::Statistics; статистичне моделювання; зайнятість; якість зайнятості; ринок праці; метод головних компонент; фактори формування; statistical modeling; employment; quality of employment; labor market; method of main components; factors of formation